Psychosocial stressors, accelerated biological aging, and multiple morbidities: Evidence from an age-diverse sample - Gabriele Ciciurkaite; Byungkyu Lee; Siyun Peng; Maleah Fekete; Colter Mitchell; Brea L. Perry (PLoS ONE, 2026)
Exposure to psychosocial stress is a well-established risk factor for poor health and premature mortality, yet most research has focused narrowly on single sources of stress without simultaneously modeling multiple stress exposures occurring across the life span. Using data from a state-representative sample of 2,267 adults ages 18–103, we examined associations between four psychosocial stressors – adverse childhood experiences (ACEs), stressful life events, chronic financial strains, and everyday discrimination – and DNA methylation-based biological aging clocks (GrimAge2 and DunedinPACE) alongside six indicators of physical and mental health outcomes. All stressors were associated with accelerated epigenetic aging and poorer health when examined individually. However, when considered simultaneously, financial strains and everyday discrimination emerged as more consistent predictors across all outcomes, relative to childhood adversity and stressful events in adulthood. Overall, stressor effects were more pronounced for mental health compared to physical health or biological aging. These findings highlight the importance of considering multiple sources of stress on varying indicators of aging, disease, and distress to fully account for the health significance of stress exposure.